Assessment of marine radiological impact after an hypothetical nuclear accident in Eastern Mediterranean Sea - Eleftheriou, Georgios; Tsabaris, Christos; Tsiaras, Konstantinos; Triantafyllou, Georgios (HNPS Advances in Nuclear Physics, 2023)
The consequences after an hypothetical nuclear accident at the Akkuyu Nuclear Power Plant in the region of Eastern Mediterranean Sea are presented. The dispersion of the radioactive plume in the sea is simulated applying a regional hydrodynamic/Lagrangian drift model and the radioecological impact is estimated after the release of 137Cs, 238Pu and 131I. The doses to marine biota and the human habitants of the affected regions are presented, while the sensitivity analysis of the results revile the most vulnerable features of this marine environment.